Damage-reliability approach for fatigue crack propagation in MDPE gas pipe - Berkas, Khaoula; Chaoui, Kamel (Zielona Góra: Uniwersytet Zielonogórski)
Fatigue crack propagation tests are carried out on arc-shaped specimens prepared from MDPE gas pipes. Damage zone characterization is achieved using the diamond wafer sectioning technique from partially propagated and prematurely arrested cracks. Damage ahead of the crack-tip is used to assess a damage parameter and reliability based on statistical laws and subsequent use the PHIMECA Software.
Keywords: MDPE gas pipe; fatigue crack propagation; damage zone; limit state function; Reliability Index